2018
DOI: 10.1016/j.marpolbul.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

In situ microbial remediation of crude oil-soaked marine sediments using zeolite carrier with a polymer coating

Abstract: Marine oil spill pollution is an important environmental problem in the world, especially crude oil-soaked marine sediments, because they are difficult to be remediated. In this study, in situ bioremediation of oil-soaked sediment was performed in the middle of the Bohai Sea. Oil-degrading bacteria were adsorbed on powdery zeolite (PZ)/granular zeolites (GZ) surfaces and then wrapped with poly-γ glutamic acid (γ-PGA). Settling column and wave flume experiments were conducted to model marine conditions and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…However, the scientific community is torn between the actual effects of bioaugmentation. The introduction of allochthonous microorganisms in field studies for the bioremediation of oil contaminated sediments has shown little enhancement of biodegradation in some cases [16][17][18], while other research studies support the technique's effectiveness on hydrocarbon bioremediation [19][20][21][22][23]. Allochthonous microorganisms might be equipped to battle hydrocarbon pollution but there are several factors to be considered for an effective application.…”
Section: Engineered Bioremediation 21 Bioaugmentationmentioning
confidence: 99%
“…However, the scientific community is torn between the actual effects of bioaugmentation. The introduction of allochthonous microorganisms in field studies for the bioremediation of oil contaminated sediments has shown little enhancement of biodegradation in some cases [16][17][18], while other research studies support the technique's effectiveness on hydrocarbon bioremediation [19][20][21][22][23]. Allochthonous microorganisms might be equipped to battle hydrocarbon pollution but there are several factors to be considered for an effective application.…”
Section: Engineered Bioremediation 21 Bioaugmentationmentioning
confidence: 99%
“…Presently, there are various approaches for oil/water separation, including chemical methods (dispersion and in situ burning), , physical methods, , and biological methods. Due to their ease of operation, cost-effectiveness, and recyclability, absorbents have been one of the most promising candidates for oil/water separation. The traditional absorbent materials are mostly activated carbon, , polypropylene sponges, biomass materials, zeolites, and other absorbent materials with microporous structures. However, in some cases, there are many drawbacks, such as poor selectivity, low adsorption capacity, slow adsorption rate, and low separation efficiency (SE) on these absorbent materials, which restrict their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have widely reported many physical, chemistry, and bioremediation technologies. Compared to physical and chemical methods, microbial remediation has more advantages of low cost, high efficiency, and sustainability ( Kujawinski et al, 2011 ; Paniagua-Michel and Fathepure, 2018 ; Zhao et al, 2018 ; Poddar et al, 2019 ; Socolofsky et al, 2019 ). Bacteria are better oil degraders than other microorganisms ( Das and Chandran, 2011 ; Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%